2011
DOI: 10.1007/s11670-011-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vitamin D levels and vitamin D receptor polymorphisms are associated with survival of non-small cell lung cancer

Abstract: Objective: Vitamin D and its receptor (VDR) involve in multiple cellular processes and play an important role in the initiation and progression of malignancy. Thus we hypothesized that plasma vitamin D levels and single nucleotide polymorphisms (SNPs) in VDR may be of prognostic significance in non-small cell lung cancer (NSCLC).Methods: We examined plasma 25-hydroxyvitamin D [25(OH)D] levels in 87 patients diagnosed with NSCLC using enzyme-linked immunosorbent assay (ELISA) and genotyped seven potentially fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Similarly, a US study of 447 early stage non-small cell lung cancer patients also observed longer survival for those with higher serum 25(OH)D at diagnosis, however the association was not statistically significant (10). In contrast, higher serum 25(OH)D at diagnosis was associated with shorter survival time in a Chinese study of 87 non-small cell lung cancer cases (12). No association between serum 25(OH)D and survival was observed for 294 patients with advanced stage non-small cell carcinoma (11), suggesting that vitamin D may be less protective for later stage, more aggressive lung tumors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, a US study of 447 early stage non-small cell lung cancer patients also observed longer survival for those with higher serum 25(OH)D at diagnosis, however the association was not statistically significant (10). In contrast, higher serum 25(OH)D at diagnosis was associated with shorter survival time in a Chinese study of 87 non-small cell lung cancer cases (12). No association between serum 25(OH)D and survival was observed for 294 patients with advanced stage non-small cell carcinoma (11), suggesting that vitamin D may be less protective for later stage, more aggressive lung tumors.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies observed better survival among lung cancer cases with higher circulating 25(OH)D measured shortly after diagnosis (9, 10), but other studies observed that higher 25(OH)D concentration at diagnosis was not association with survival (11) or associated with worse survival (12). To our knowledge no other studies have examined pre-diagnostic serum 25(OH)D in relation to survival among lung cancer cases.…”
Section: Introductionmentioning
confidence: 98%
“…The VDR TaqI and BsmI variants have been associated with survival in non-small cell lung cancer patients (105), and an international multicenter case-control study consortium (the Genes, Environment, and Melanoma (GEM) Study) found significant associations with melanoma mortality for 8 common VDR variants (106) ( Table 2). Mortality was also associated with the vitamin D binding protein gene, GC, and RXRA in the Nurses' Health Study and Health Professionals Followup Study (107) ( Table 2).…”
Section: Vitamin D-related Genesmentioning
confidence: 99%
“…The vitamin D-binding protein (encoded by the group-specific component , GC gene) mainly promotes transportation of vitamin D metabolites [11]. Laboratory studies showed that high 1,25(OH) 2 D levels can inhibit differentiation and proliferation in human lung cancer cell lines [12], and circulating 25(OH)D level may predict early-stage NSCLC patients’ survival [13,14]. Vitamin D-related genes have highly polymorphic genotypes in different human populations.…”
Section: Introductionmentioning
confidence: 99%